Preferential expression of an alpha-tubulin gene of Arabidopsis in pollen. - Carpenter, J L (1992)
The pool of tubulin protein in tissues of Arabidopsis is provided by the expression of multiple alpha-tubulin (TUA) and beta-tubulin genes. Whereas most tubulin genes are expressed in many tissues, previous evidence suggested that the TUA1 gene might be expressed primarily in pollen. We now report a detailed analysis of TUA1 expression during Arabidopsis development. In RNA from tissues of dissected flowers, TUA1 transcripts were detected only in stamens and mature pollen. Chimeric genes containing TUA1 5' flanking DNA fused to the beta-glucuronidase (GUS) coding region were used to create transgenic Arabidopsis plants. Plants containing a chimeric gene with 533 bp of 5' flanking sequence were analyzed by histochemical assay to localize GUS expression within the plant. The blue product of GUS enzyme activity accumulated very rapidly in postmitotic pollen grains. Much lower levels of GUS activity were detected in anthers with uninucleate pollen grains, in flower receptacles, and in a few vegetative tissues. Analysis of 5' deletions of the TUA1 promoter suggested that 97 bp of 5' flanking DNA is sufficient to drive GUS expression in pollen and young anthers, whereas at least 380 bp is required to detect GUS expression in the receptacle. Examination of the TUA1 promoter sequence revealed several motifs that are repeated within the TUA1 promoter and are similar to sequences in other pollen-specific promoters.